The wellsprings of the middle years a Filipino perspective - Abrenica, Alexa P. (1996)
Many people associate the middle years with negative experiences and the proverbial mid-life crisis. But the middle years can also be experienced as a delightful, liberating, exhilarating period. The paper focuses on these positive aspects of midlife. A survey of midlifers found that majority of the respondents described the middle years as challenging, exciting, a time of great expectation, and fulfillment. The paper summarizes the various wellsprings of the middle years in the acronym SPACES which stands for Spiritual life, Physical health, Attitude towards life/aging, Confidence and creativity, Emotional health, and Social network and satisfying work. The paper proposes that the difference between people who seem to experience negative mid-life years and those who experience positive ones lies in whether thay have filled up the SPACES in their lives.
Includes bibliographical references (pages 111-112).